2022
DOI: 10.1093/ehjopen/oeac053
|View full text |Cite
|
Sign up to set email alerts
|

Left-atrial long-axis shortening allows effective quantification of atrial function and optimized risk prediction following acute myocardial infarction

Abstract: Background Deformation imaging enables optimized risk prediction following acute myocardial infarction (AMI). However, costly and time-consuming post processing have hindered widespread clinical implementation. Since manual left ventricular long axis strain (LV LAS) has been successfully proposed as a simple alternative for LV deformation imaging, we aimed at the validation of left atrial (LA) LAS. Methods The AIDA STEMI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These volumes were derived by subtraction of minimal from maximal chamber volumes. Furthermore, long-axis strain (LAS) was assessed for all four cardiac chambers 16,17 (online supplementary Figure S1). Furthermore, RT phase-contrast imaging 18,19 was performed at the level of the PA above the pulmonary valve plane for the assessment of RV stroke and peak flow volumes at rest and during exercise stress.…”
Section: Cardiovascular Magnetic Resonance-derived Cardiac Functional...mentioning
confidence: 99%
“…These volumes were derived by subtraction of minimal from maximal chamber volumes. Furthermore, long-axis strain (LAS) was assessed for all four cardiac chambers 16,17 (online supplementary Figure S1). Furthermore, RT phase-contrast imaging 18,19 was performed at the level of the PA above the pulmonary valve plane for the assessment of RV stroke and peak flow volumes at rest and during exercise stress.…”
Section: Cardiovascular Magnetic Resonance-derived Cardiac Functional...mentioning
confidence: 99%
“…Advances in CMR imaging introduced in the HFpEF Stress Trial [ 12 , 13 ] demonstrated that RT-CMR imaging allows the transition of exercise-stress testing into the already broad spectrum of CMR imaging. Although RT-CMR does not allow for detailed deformation imaging assessment of the three atrial phases, our results show that it accurately reflects LA longitudinal function (and potentially increased active contractility during exercise), which allows for the identification of early stage HFpEF based on surrogate estimation (LV/LA LAS) of global LV and LA longitudinal strains [ 20 ]. This allows the translation of longitudinal deformation imaging to physiological exercise-stress assessments [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…RT-CMR imaging was performed at rest and during exercise-stress using a bSSFP sequence combined with an undersampled radial encoding scheme [ 13 ]. Left atrial (LA) and ventricular (LV) long axis strains (LAS) were assessed in the 2 and 4 CV using OsiriX MD (Pixmeo SARL, CH-1233 Bernex, Switzerland) [ 19 , 20 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…This highlights the need for functional parameters in the diagnosis of HFpEF which is also reflected in an overall poorer diagnostic accuracy for masked HFpEF using LAV PCWP. This may point toward a new approach for non-invasive PCWP calculation in the future, including a more dynamic parameter, such as LAS which can be measured as easily as LAV or LAA [28] .…”
Section: Discussionmentioning
confidence: 99%